Development of a Specfic Pcr-Based Assay for the Detection of Escherichia Coli O157: H7 - Gurnam Singh, Sushil Kaur (2004)
A total of nine Escherichia coli O157:H7 isolates were originally isolated from imported Indian beef purchased from local retail markets. These nine Escherichia coli O157:H7 isolates were confirmed as Escherichia coli O157:H7 by their positive growth characteristics on Rainbow agar O157 and PCR assay for the detection of the presence of the H7 (fliC) gene unique to Escherichia coli O157:H7. Published specific primers FLICH (625 bp) of the fliC gene encoding the H7 antigen were utilized in the specific PCR assay. Three of the Escherichia coli O157:H7 isolates were selected for the amplification of their H7 (fliC) gene. The amplicon of the PCR assay were successfully cloned into pGEM-T vector and sequenced. The sequence of the Escherichia coli O157:H7 that was obtained from sequencing was analyzed. This sequence was identified using Basic Local Alignment Search Tools (Blast) program. Based on the sequence obtained, primer pairs were designed to detect the Escherichia coli O157:H7, but only Sk7 and Sk8 were found to be specific for detection of locally isolated Escherichia coli O157:H7. Sk7 and Sk8 produced an amplicon size of 520 bp and 603 bp respectively against all tested locally isolated Escherichia coli O157:H7. Both new primers were specific against Escherichia coli O157:H7, as they did not produce any amplicons from the 32 isolats representing 20 different bacterial species. DNA hybridization analysis of 10 other bacterial species, including E. coli, Salmonella and other isolates showed that the probe (SkP) reacted only with Escherichia coli O157:H7 isolates.